Contact relaxation phenomena in nano-structured composite materials - Boyko, Yu.I.; Volosyuk, M.A.; Volosyuk, A.V.; Rokhmanov, N.Ya. (Functional Materials, 2015)
There are discussed physical mechanisms of some effects related to both nano-material granularity and existence of the strongly branched contact area separating the nano-size grains. In the area the relaxation processes take place including electron level, i.e. substantial reconstruction of the electron subsystem and charge state in the grain boundary area. Estimations have been carried out for a concrete nano-composite material formed by metal and semiconductor substances with different charge volume density in the conductivity band. On the basis of the estimations and discussion, conclusion has been done on the possibility for controlled varying the phase and structure state as well as physical properties (magnetic, electrical, optical, etc.) of the nano-structured material by changing the granularity and composition.